Efficacy evaluation of a novel vectorized anti‐tau antibody, targeting a C‐terminal phospho‐tau epitope, using systemic dosing of a blood brain barrier penetrant AAV capsid in mouse models of tauopathies. (20th December 2022) - Liu, Wencheng; Paranjpe, Maneesha; Holth, Jerrah; Clarke, Blaise; Thompson, Jeffery; Clement, Joe; Knoll, Elisabeth; Chung, Charlotte; Adeluyi, Adewale; Powers, Alex; Kurella, Vinodh; Kavanagh, Dillon; et al.
Abstract: Background: Anti‐tau immunotherapy has become a promising therapy for Alzheimer's disease (AD) and tauopathies. With the hypothesis that tau pathology spreads via cell‐to‐cell transmission, including trans‐synaptic propagation, success of anti‐tau immunotherapy relies, in part, on the identification of efficacious antibodies and their delivery to affected or vulnerable brain regions with sufficient or enhanced exposure in the CNS. We have previously demonstrated broad distribution and expression of vectorized anti‐tau antibodies in the mouse brain using a blood brain barrier penetrant capsid, VOY101, administered intravenously (IV). Method: Several novel anti‐tau antibodies that met the target profile have been generated and are being evaluated in vivo (Liu et al, submitted as a separated abstract in AAIC 2022). Result: One of the antibodies discovered, antibody 1, exhibits strong affinity for PHF‐tau, demonstrates specific binding to tau pathology on brain sections of AD and PSP patients, and potently prevents PHF seeding and propagation in vitro and in vivo. This antibody recognizes a phospho‐specific epitope in the C‐terminal region of tau and shows significant reduction of tau pathology in an AD‐PHF induced P301S hippocampal seeding and propagation model. Furthermore, we have vectorized antibody 1 into an AAV expression vector with by BBB penetrant capsid and are evaluating it in two independent mouse models of tauopathy. Conclusion: This gene therapy‐based approach has potential advantages over traditional passive immunization, including 1) continuous expression of antibody in the central nervous system (CNS) after a single gene therapy administration compared to repetitive administrations of high dose of antibody by passive immunotherapy; 2) increased CNS exposure of tau antibody relative to passive immunotherapy; and 3) the potential to target intracellular tau aggregates which are less effectively accessed by passively delivered antibody. These results add to accumulating evidence that systemic dosing of a vectorized anti‐tau antibody using a BBB‐penetrant AAV capsid results in reduced tau pathology and may represent a new single‐dose therapeutic strategy for treating various tauopathies.